2016
DOI: 10.3109/10641963.2015.1116542
|View full text |Cite
|
Sign up to set email alerts
|

The inter-arm systolic blood pressure difference and risk of cardiovascular mortality: A meta-analysis of cohort studies

Abstract: The inter-arm systolic blood pressure difference (SBPD) is recommended to be in relation to potential cardiovascular disease (CVD). Previous studies yielded controversial results about the association between an inter-arm SBPD ≥ 10 mmHg or ≥15 mmHg and the risk of cardiovascular mortality. Therefore, we conducted this meta-analysis to investigate this association. We searched PubMed and Embase databases through December 31, 2014, and examined the references of retrieved articles to identify relevant cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…This view is supported by some published work (Olmedillas et al, 2010) and it has been suggested that larger circumference arms may be associated with higher measured SBP (Loenneke et al, 2016). Furthermore, because of the widely reported potential significance of inter-arm SBP differences as a predictor of cardiovascular morbidity (Cao et al, 2015;Tokitsu et al, 2015;Zhou et al, 2016;Kranenburg et al, 2017;Hirono et al, 2018) it was believed that the issue concerning the role that handedness might play in such inter-arm pressure differences was of significance and should be specifically addressed. A third motivating factor was that most prior assessments of inter-arm pressure differences focused on either older persons or those with already present cardiovascular symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This view is supported by some published work (Olmedillas et al, 2010) and it has been suggested that larger circumference arms may be associated with higher measured SBP (Loenneke et al, 2016). Furthermore, because of the widely reported potential significance of inter-arm SBP differences as a predictor of cardiovascular morbidity (Cao et al, 2015;Tokitsu et al, 2015;Zhou et al, 2016;Kranenburg et al, 2017;Hirono et al, 2018) it was believed that the issue concerning the role that handedness might play in such inter-arm pressure differences was of significance and should be specifically addressed. A third motivating factor was that most prior assessments of inter-arm pressure differences focused on either older persons or those with already present cardiovascular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This meant that there was little data on young and apparently healthy adults. Furthermore, because of the widely reported potential significance of inter-arm SBP differences as a predictor of cardiovascular morbidity (Cao et al, 2015;Tokitsu et al, 2015;Zhou et al, 2016;Kranenburg et al, 2017;Hirono et al, 2018) it was believed that the issue concerning the role that handedness might play in such inter-arm pressure differences was of significance and should be specifically addressed. This led to the working hypothesis that the magnitude of cuff pressures needed to compress the underlying brachial artery in determining SBP would be greater in the dominant arm thereby rendering the dominant arm to have a greater SBP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is recommended to measure blood pressure (BP) in both arms at patients’ initial evaluation because there are differences in the BP values measured in both arms . A review of series reported prevalences of the IAD ranging from 12.0% to 18.4% for a sIAD ≥20 mm Hg and from 13.0% to 33.7% for a dIAD ≥10 mm Hg in different populations; substantial evidence has indicated that IAD, especially sIAD, is an independent risk factor for ischemic stroke, left ventricular hypertrophy, and other fatal and nonfatal cardiovascular events . It is still unclear whether coronary heart disease (CHD) or cerebrovascular disease is more associated with sIAD/dIAD of 10 or 15 mm Hg or more.…”
Section: Introductionmentioning
confidence: 99%